Nuclear hormone receptors: Ancient 9aaTAD and evolutionally gained NCoA activation pathways - Piskacek, Martin; Havelka, Marek; Jendruchova, Kristina; Knight, Andrea (The Journal of steroid biochemistry and molecular biology, 2019)
In higher metazoans, the nuclear hormone receptors activate transcription trough their specific adaptors, nuclear hormone receptor adaptors NCoA, which are absent in lower metazoans. The Nine amino acid TransActivation Domain, 9aaTAD, was reported for a large number of the transcription activators that recruit general mediators of transcription. In this study, we demonstrated that the 9aaTAD from NHR-49 receptor of nematode C.elegans activates transcription as a small peptide. We showed that the ancient 9aaTAD domains are conserved in the nuclear hormone receptors including human HNF4, RARa, VDR and PPARg. Also their small 9aaTAD peptides effectively activated transcription in absence of the NCoA adaptors. We also showed that adjacent H11 domains in ancient and modern hormone receptors have an inhibitory effect on their 9aaTAD function.
Keywords: hepatocytární jaderný faktor 4; Caenorhabditis elegans Proteins; Animals; Retinoic Acid Receptor alpha; PPAR; RARa; VDL; sekvence aminokyselin; Caenorhabditis elegans; PPAR gama; Transcriptional Activation; KIX; proteinové domény; lidé; signální transdukce; Amino Acid Sequence; Protein Domains; receptory cytoplazmatické a nukleární; Signal Transduction; Models, Molecular; Receptors, Calcitriol; peptidy; molekulární modely; Receptors, Cytoplasmic and Nuclear; proteiny Caenorhabditis elegans; 9aaTAD; Sequence Alignment; CBP; HNF4; aktivace transkripce; MED15; alfa receptor kyseliny retinové; zvířata; PPAR gamma; Hepatocyte Nuclear Factor 4; Peptides; receptory kalcitriolu; sekvenční seřazení; Humans